Dead until dark eaudiobook - Harris, Charlaine (Sookie Stackhouse, 2007)
Anthony Award winner Charlaine Harris' New York Times and USA Today best-selling Sookie Stackhouse novels entice countless fans with an irresistible mixture of vampire romance, beguiling mystery, and old-fashioned Southern charm. Vampires have officially "come out of the coffin," and Miss Sookie can't wait for one to come her way.